1980
DOI: 10.1073/pnas.77.9.5502
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an electrochemical proton gradient in Streptococcus cremoris by lactate efflux.

Abstract: Recently an energy-recycling model was proposed that postulates the generation of an electrochemical gradient in fermentative bacteria by carrier-mediated excretion of metabolic end products in symport with protons. In this paper experimental support for this model is given. In batch cultures of Streptococcus Uptake studies with the lipophilic cation tetraphenylphosphonium demonstrated that lactate efflux increased the electrical potential across the membrane by 51 mV. The generation of an electrical potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(91 citation statements)
references
References 16 publications
2
89
0
Order By: Relevance
“…Acids, however, may uncouple energy generation from biomass formation (Baronofsky et al 1984;Tuttle & Dugan 1976;Verduyn et al 1990b), although this probably depends to a major extent on the culture pH. Alternatively, export of acids may yield energy under certain conditions, as shown for lactate efflux by Streptococcus cremoris (Otto et al 1980). In contrast, yeasts only form two main fermentation products under anaerobic conditions, ethanol and glycerol, which are neutral and leave the cell by passive diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…Acids, however, may uncouple energy generation from biomass formation (Baronofsky et al 1984;Tuttle & Dugan 1976;Verduyn et al 1990b), although this probably depends to a major extent on the culture pH. Alternatively, export of acids may yield energy under certain conditions, as shown for lactate efflux by Streptococcus cremoris (Otto et al 1980). In contrast, yeasts only form two main fermentation products under anaerobic conditions, ethanol and glycerol, which are neutral and leave the cell by passive diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…Konings and colleagues (Michels et al, 1979;Otto et al, 1980Otto et al, , 1982ten Brink & Konings, 1980) have provided evidence for an ' energy recycling model ' in Lactococcm lactis where the lactate ion, which is impermeable to the cell membrane, leaves the cell via a membrane carrier in symport with more than one proton. The energy recycling model is an extension of the chemiosmotic model presented by Mitchell (1963) and postulates that carriermediated excretion of end-products can lead to the generation of an electrochemical gradient across the cell membrane, thereby providing energy to the cell.…”
Section: S G Dashper a N D E C R E Y N O L D Smentioning
confidence: 99%
“…The generally accepted view is that in these organisms, the pmf and/or smf is generated by the action of the membrane-bound ATPase. However, recent studies have revealed that primary metabolic energy generation is not the only process by which a pmf or smf can be generated (Otto et al 1980;Poolman 1990;Konings et al 1994). In fermentative bacteria, a pmf or smf can be generated by secondary transport processes and, by analogy, these processes are called 'secondary metabolic energy generation' (Fig.…”
Section: Abstract Metabolic Energy · Proton Motive Force · Secondarymentioning
confidence: 99%